Impediments to International Air Transportation Services in Japan: Measuring the Border Effect in Main Japanese Airports - Takamune Fujii; Mariko Futamura (European Regional Science Association (ERSA), 2006)
In this paper, we investigate the effectiveness of international passenger air transportation services in Japan by quantifying the "border effect." In order to measure the border effect, we employ the basic gravity model for explaining intra- and international passenger flow in Japan as a benchmark model at first. And then, "border effect" dummy variable is introduced to quantify the diminishing effect to passenger flow in case of international travel. If the dummy variable has negative and statistically significant coefficient, international passenger flow in Japan is smaller than intranational flow. Bilateral passenger flow data among main Japanese airports and between Japanese airport and foreign one is used for our empirical estimation, and the dummy variable shows negative coefficient. This result implies that international passenger flow is diminished by some impediments such as political regulation, institutional inefficiency, and so on. For instance, entry barrier for new carrier or market access restriction to airport services in international airline may have decreasing effect to international passenger flow because of high services cost, and poorly established infrastructure like international air terminal or tiresome immigrant / emigrant procedure may decline passengers' incentives for traveling abroad or visiting Japan. Unfortunately we cannot specify the reason why international passenger flow is so small because we just measure the difference between international and intranational flow. However, if there are really some impediments in international air transportation services, those may be disadvantageous for Japanese airports to compete with other Asian international hub airports.
Keywords: 330